PENGARUH PENGARUH PERCEIVED OF USEFULNESS , PERCEIVED EASE OF USE, DAN PERCEIVED RISK TERHADAP CONTINUANCE INTENTION PADA PENGGUNAAN DIGITAL PAYMENT DI PROVINSI BENGKULU (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2023)
Increasingly massive technological developments have been used in various aspects of people's lives, including in the financial sector. Non-cash payments have been supported by technological developments so many digital payment applications have developed in the community. However, along with technological developments in the financial sector, it has not been evenly distributed to all Indonesian residents. This also happened in Bengkulu Province, it was recorded that only around 0.13% of the total population, even this amount was not followed by a good volume of transactions. So this study analyzes the effect of Perceived Usefulness, Perceived Ease of Use, and Perceived Risk on Continuance Intention on the Use of Digital Payments in Bengkulu Province. This study uses a quantitative method with the SmartPLS analysis tool. The results of the study show that Perceived Usefulness and Perceived Ease of Use do not affect Continuance Intention on the Use of Digital Payments in Bengkulu Province. Meanwhile, the Perceived Risk variable has an effect of 2.128 on Continuance Intention on the Use of Digital Payments in Bengkulu Province.